PRIMARY MALIGNANT BONE TUMOR CHONDROSARCOMA OF THE STERNUM - Suyasa, I Ketut; Satria Nugraha, Gede Ketut Alit; Wiratnaya, I Gede Eka (E-Jurnal Medika Udayana, 2019)
The primary sternal tumor is rare, with its incidence representing 0.6-0.9% of all primary bone tumors. The current study aimed to report a rare case of chondrosarcoma in the body of sternum, which was successfully treated.Chondrosarcoma is a primary malignant bone tumor that is composed of cartilage-producing cells or chondrocytes. It is one of the most challenging bone tumors to diagnose and treat. These cartilage lesions may have inconclusive features, necessitating close follow-up or biopsy. On radiographs, the radiologist should look for aggressive features such as focal erosion with abrupt margins, periosteal reaction or cortical breakthrough. In our case, none of the typical radiographic changes of chondrosarcoma appeared on chest imaging studies, and the diagnosis was based on biopsy. Surgery is the best therapeutic option for a sternal tumor. In some cases, radiation and or chemotherapy may be used pre- or post-operatively. Chondrosarcoma is a malignant cartilage-forming tumor of bone. It is rarely found in the sternum, making the case presented herein rare and the diagnosis to be complicated. Multidisciplinary management of this case is necessary to make diagnosis and treatment. Keywords: Chondrosarcoma, Sternum, Sternal tumor, rare bone tumor, Primary malignant bone tumor, Tumor diagnostic, Tumor histopathology